Cesarean section trends in the Nordic Countries – a comparative analysis with the Robson classification - Pyykönen, Aura; Gissler, Mika; Løkkegaard, Ellen; Bergholt, Thomas; Rasmussen, Steen C.; Smárason, Alexander; Bjarnadóttir, Ragnheiður I.; Másdóttir, Birna B.; Källén, Karin; Klungsoyr, Kari; Albrechtsen, Susanne; Skjeldestad, Finn E.; et al. (Acta obstetricia et gynecologica Scandinavica, 2017)
Introduction The cesarean rates are low but increasing in most Nordic countries. Using the Robson classification, we analyzed which obstetric groups have contributed to the changes in the cesarean rates. Material and methods Retrospective population‐based registry study including all deliveries (3 398 586) between 2000 and 2011 in Denmark, Finland, Iceland, Norway and Sweden. The Robson group distribution, cesarean rate and contribution of each Robson group were analyzed nationally for four 3‐year time periods. For each country, we analyzed which groups contributed to the change in the total cesarean rate. Results Between the first and the last time period studied, the total cesarean rates increased in Denmark (16.4 to 20.7%), Norway (14.4 to 16.5%) and Sweden (15.5 to 17.1%), but towards the end of our study, the cesarean rates stabilized or even decreased. The increase was explained mainly by increases in the absolute contribution from R5 (women with previous cesarean) and R2a (induced labor on nulliparous). In Finland, the cesarean rate decreased slightly (16.5 to 16.2%) mainly due to decrease among R5 and R6–R7 (breech presentation, nulliparous/multiparous). In Iceland, the cesarean rate decreased in all parturient groups (17.6 to 15.3%), most essentially among nulliparous women despite the increased induction rates. Conclusions The increased total cesarean rates in the Nordic countries are explained by increased cesarean rates among nulliparous women, and by an increased percentage of women with previous cesarean. Meanwhile, induction rates on nulliparous increased significantly, but the impact on the total cesarean rate was unclear. The Robson classification facilitates benchmarking and targeting efforts for lowering the cesarean rates.